(untitled) (mathematica didactica, 2018)
The present article aims to show that the investigation of historical drawing instruments offers basic insights into current didactic topics. In the course of the article, references to modeling are worked out. The concept of a conglomerate of ideas is introduced and placed in relation to the theory of instrumental genesis. Important results of an empirical study are summarized. Two key questions of the study were: Which learning processes happen when using and forming an idea-conglomerate in the classroom? How does the instrumental genesis of a drawing device take place? Finally, suggestions for a media-based mathematics education are given.